Community engagement: Barriers and drivers in South African higher education - Johnson, B.J. (South African Journal of Higher Education, 2020)
Community engagement professionals experience numerous barriers even though community engagement is the third mission of the university alongside first, teaching and learning, and second, research. Community engagement professionals often refer to community engagement as the “stepchild” of higher education. Yet there are also inter-related successful drivers. This article identifies the barrier–driver duality and makes a case for their systemic interconnectedness, an area that has thus far been underexplored. A prominent barrier for community engagement professionals is that there is a lack of substantive conceptualisation of community engagement, intensified by the contradictory placing of community engagement within community and university structures. Interconnected to such barriers, prominent drivers demonstrate the value of scholarly, reflective practice and to enhance the leadership role of the South African Higher Education Community Engagement Forum, inclusive of the views of pertinent members such as academic leaders, students and communities.